Body surface area estimation: Cross validation of several prediction equations - Wickramasinghe, V.P.; Sathyadas, G.; Lamabadusuriya, S.P. (My University, 2009)
Background Body surface area (BSA) is used in clinical practice to prescribe medication, standardize measured parameters etc. Normogram has been the gold standard. However, there are several prediction equations in the published literature. A simple method giving an accurate estimation would help to assess BSA in day to day clinical practice efficiently. Objective To assess the accuracy of different equations for the estimation of BSA in a group of Sri Lankan children. Method Data collected in 3 different school surveys carried out between 2002 and 2005 were used. BSA estimated by 9 prediction equations described in the literature were compared with the BSA assessed by normogram. Results Two thousand three hundred and thirty eight girls and 639 boys, between the ages of 5-16 years, were assessed. The mean ages of the boys and girls were 10.3±1.47 years and 11.5±2.47 years respectively. The highest mean BSA estimation was given by Gehan & George equation (boys 1.14±0.20m2 and girls 1.2 ± 0.25m2) and lowest by Yu et al (boys 1.08±0.20m2 and girls 1.13±0.25m2). Estimates correlated highly with BSA assessed by normogram. When the estimates were compared with normogram, equation of Mattar gave the highest bias for both groups (females 0.0152m2 and males 0.0177m2). Mosteller equation gave relatively low bias (females 0.0077m2, and males 0.0072 m2). Conclusions All equations gave very good agreement between each other. Out of the equations, easiest to use in day to day clinical practice is the equation described by Mosteller. The maximum bias in estimation would lead to less than 5% error in determining drug doses which is negligible in day to day clinical practice. Mosteller equation is suitable for routine clinical use.